Porpax Meirax (Par. et Reichb. F. ) K. & P. (Orchidaceae) First Report of its Occurrence in India - Deori, N. C.; Malhotra, C. L. (Indian Forester, 1975)
Porpax meirax (Par. et Reichb. f. ) K. & P., an epiphytic orchid, hitherto recorded from Bhutan, Sikkim, Tenasserim; Laos, Malaya & Thailand, is recorded here from India for the first time.